LEGAL BASIS OF ORGANIZING A HEALTHY LIFESTYLE OF THE POPULATION IN UZBEKISTAN. - Sattorova Dildora Gapparovna; Khojiakhmedova Sitorabonu (Ta'lim innovatsiyasi va integratsiyasi, 2023)
It is known that the legal basis of the organization of a healthy lifestyle of the population is already a relatively new branch of law in the world. It has become a component of the legal system of many countries and the legal culture of the population. International standards in the field of health were first established in the Charter (Constitution) of the World Health Organization (WHO), which defines the main goal of the WHO as "Achieving the highest possible level of health for all peoples". Therefore, the Code of Public Health adopted in the Republic of Uzbekistan also has great importance.